Das multilinguale fachsprachliche Korpus TK-NHH – Eine korpusbasierte Fallstudie über die explicitation hypothesis anhand von ins Deutsche und Englische übersetzten Rechtstexten - Simonnæs, Ingrid (HERMES - Journal of Language and Communication in Business, 2011)
The present study is a case study about the explicitation hypothesis in legal translations into German and English by means of a corpus-based approach and will present preliminary ﬁndings. After the introduction, I ﬁrst describe the National Translator Accreditation Exam (statsautorisert translatøreksamen) in Norway from which the texts for the TK-NHH translation corpus are chosen. Next I describe the aim of the case study which is to investigate the explicitation hypothesis by means of the TK-NHH translation corpus. In the method section, I discuss brieﬂy the inﬂuence and applicability of corpus linguistics on translation studies. Finally, in the case study, I investigate both German and English legal translations in the TK-NHH translation corpus with regard to one speciﬁc feature that is claimed to be universal: explicitation. In this case study, I have chosen the explicitation of proper names of culture-speciﬁc legal institutions (e.g. courts). The results in both languages show a variety of explicitation together with no explicitation and thus seem to substantiate earlier ﬁndings, but now with regard to translation solutions from Norwegian.